Report of proposed new design for the Actors Studio Academy of Performing Arts at No.18, Section 11/1, Jalan University, 47200, Petaling Jaya, Selangor Darul Ehsan / Nadiah Md Saad - Md Saad, Nadiah (Faculty of Architecture, Planning and Surveying, 2006)
This project inspired to provide a new space for The Actors Studio to establish another academy in a new location where the teaching and learning of performing arts can be introduced to a new community and possibly expand its support group and add member to the theatre company. The new academy should have a comfortable space with enough space to house its classes and activities. The activities provided by The Actors Studio Academy (TASA) include classes on different types of performing arts, as well as workshops on writing, directing, set design, and production programs. The Actors Studio Academy also provides space for other organizations to hold their activities as well. It is not only restricted for the members and students of TASA but also for other independent production houses or organizations in need of rehearsal space or a place to hold meetings or work sessions. There is an information and registration counter provided for new students and inquiries. Aside from that, it also provides services for anything involved in theatre production and performing arts. Furthermore, TASA also holds small productions which were created by students of classes or programs held. This is to show the benefits of the academy and it will also show that TASA has its goals and prove that they can achieve it.